Proteinuria due to increased dose of deferasirox in a pediatric patient with thalassemia major: case report - Sarbay, Hakan; Kara, Mehtap Akbalik (International Journal of Contemporary Pediatrics, 2018)
Deferasirox is an iron chelator that used in B-thalassemia in worldwide. Nephrotoxicity is one of the common side effects of the deferasirox. Nephrotoxicity can be seen in the form of nephritis and tubulopathy. A 6-year-old male whose ferritin levels were above 3500 ng/mL is reported in this article. Deferasirox was increased from 30 mg/kg/day to 40 mg/kg/day because of the high levels of ferritin. In complete urinalysis of the patient after 3 weeks later +3 protein was detected, and spot urine protein/creatinine ratio was 2.5. In patient without symptoms and findings, deferasirox was discontinued. In his follow-ups, no proteinuria was detected in the complete urinalysis at the second week after the drug treatment was discontinued.